Pembelajaran Media Permainan Ular Tangga Untuk Meningkatkan Motivasi Belajar Ips Di Sekolah Dasar - Fatimah Thusyadiyah; Lutfi Fadilillah; Mifrohatunnisa Mifrohatunnisa (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
This study aims to develop learning media for the game of snakes and ladders in social science learning (IPS) in elementary schools to increase learning motivation and student learning outcomes. One of the problems of education is the lack of facilities and infrastructure, so teachers are required to be creative in improving the quality of learning in the classroom, such as developing learning media. One of the learning media that is interesting and overcomes student boredom in learning activities is game-based learning activities, such as the application of the snake and ladder game learning media. This study develops a snake and ladder game learning media in social science learning (IPS) in elementary schools. This research is qualitative and the method used is descriptive method. This media is directed so that learning objectives can be achieved efficiently and effectively in a happy atmosphere even though discussing difficult or heavy things.